Patchouli Oil Characteristics by Optimization Result of Distillation Time of Patchouli Leaf Dewaxing and Fermentation - Sentot Joko Raharjo; Rurini Retnowati; Soebiantoro Soebiantoro (Natural B, Journal of Health and Environmental Sciences, 2012)
The characteristic of patchouli oil of dewaxing, fermentation and time distillation toward patchouli leaves used GC-MS have been done. The aim of the study was to characterization of patchouli oil on distillation time of patchouli leaves of dewaxing and fermentation. The characteristics of patchouli oil on the distillation time for 12 hours, then the distillate collected every 2 hours showed that of the best result was the 3rd fraction collected distillate time of 12 hours with a yield of 0.56 %, light yellow color, specific gravity 0.9685 g/ mL and a refractive index of 1.5095 and patchouli alcohol of 69.56 %. Characteristics of patchouli oil on distillation time (2, 4, 6, 8, 10, 12) hours showed that of the best result was time distillation for 12 hours with a yield of 6.61 %, light yellow color, specific gravity of 0.9672 g/ mL, refractive index of 1.5082 and patchouli alcohol of 45.69 %. The other components of patchouli oil detected were alpha-gurjunene, cis-thujosene, beta-patchoulene, alpha-patchoulene, beta-caryophyllene, alpha-guaiene, seychellen, aromadendrene, beta-gurjunene, alpha-humulene, alpha-bulnesene, gemacrene-D, dehidroaromadendrene, gemacrene-A, gamma-patchoulene, valencene, viridiflorene, selina-3,7-(11)-dien, nor-patchoulenol, pogostol, illudol, globulol, beta-caryophyllen oksida, viridiflorol and ledol. Patchouli oil quality to meet requirements SNI 06-2385-2006 and ISO 3757:2002.